2016
DOI: 10.1016/j.ssmph.2016.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Maternal age and offspring health and health behaviours in late adolescence in Sweden

Abstract: In this study we investigate the relationship between maternal age at the time of birth and a variety of health behaviours and measures of health amongst young adults in contemporary Sweden. Previous research has shown that those born to younger and older mothers tend to have worse perinatal outcomes, and worse health in middle- and later adulthood. However, previous work has not examined health in early adulthood, and no studies have explored whether maternal age is related to health behaviours. Using survey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 45 publications
2
19
1
2
Order By: Relevance
“…Epidemiological and demographic studies in humans have shown a negative correlation between maternal age and children’s lifespan and health 25,27,30,45,46 . However, maternal age effects in humans can be difficult to separate from confounding environmental factors including paternal age effects, parental health, parental socio-economic status, and parental care 47-49 .…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological and demographic studies in humans have shown a negative correlation between maternal age and children’s lifespan and health 25,27,30,45,46 . However, maternal age effects in humans can be difficult to separate from confounding environmental factors including paternal age effects, parental health, parental socio-economic status, and parental care 47-49 .…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological and demographic studies in humans have shown a negative correlation between maternal age and children’s lifespan and health 25,27,30,45,46 . However, maternal age effects in humans can be difficult to separate from confounding environmental factors including paternal age effects, parental health, parental socio-economic status, and parental care 47–49 .…”
Section: Introductionmentioning
confidence: 99%
“…Female reproductive behaviours, including age at first birth (AFB), age at first sexual intercourse (AFS), age at menarche (AMC), age at menopause (AMP) and number of live births (NLB) have important implications in reproductive health and evolutionary fitness 1,2 . Some of these traits have been shown to associate with the physical and mental health of offspring 3 , and there has been growing evidence that maternal AFB is associated with increased risk of psychiatric disorder 4,5 and behavioural problems in their children 6,7 . For instance, both early and late maternal AFB are associated with an increased risk to schizophrenia (SCZ) 4 , bipolar disorder (BIP) 8 , attention-deficit/hyperactivity disorder (ADHD) 7 , autism spectrum disorder (ASD) 9 and depression 10 in offspring.…”
Section: Introductionmentioning
confidence: 99%